The use of nanoparticles in electroanalysis: an updated review. - Campbell, F; Compton, R (2010)
The use of nanoparticles in electroanalysis is an area of research which is continually expanding. A wealth of research is available discussing the synthesis, characterization and application of nanoparticles. The unique properties of nanoparticulate materials (e.g. enhanced mass transport, high surface area, improved signal-to-noise ratio) can often be advantageous in electroanalytical techniques. The aim of this paper is to provide an updated overview of the work in this field. In this review we have concentrated on the advances with regards to silver, gold, platinum, palladium, ruthenium, copper and nickel. The synthesis, characterization and practical application of these materials are discussed. We have also identified the conditions under which each metal is likely to be stable, which is likely to be a useful tool for those practising in the field. Furthermore, we have provided a theoretical overview of advances in the theoretical modelling and simulation of nanoparticle behaviour.